PERFORMANCE OF VILLAGE FUNDS ON COMMUNITY INCOME LEVELS : CASE STUDY IN NORTH MALUKU - Prince Charles Heston Runtunuwu; Lev Horodyskyj (Fakultas Hukum Universitas Malikussaleh, 2023)
This study aims to determine. To find out the factors that influence the use of village funds on the level of income and welfare of the village community Koititi South Halmahera Regency , North Maluku and to find out how much influence the Village Fund (DD) has on the welfare of the people of Koititi village, South Halmahera Regency. Village Fund Utilization Policy (DD) using qualitative research methods. Based on research results, the income and welfare of the Koititi Village community is measured based on how much benefit is generated by the Village Fund to meet the material and spiritual needs of the Koititi Village community through programs taken by the village government. The following are some of the programs in Koititi Village in 2018-2019. West Gane District, South Halmahera Regency.